Jarosław Kurski, “President of Citizens” - rhetorical analysis - Worsowicz, Monika (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter contains a rhetorical analysis of a journalistic article entitled “President of Citizens” by Jarosław Kurski. The text published in “Gazeta Wyborcza” in November 2019 was a voice in the discussion on the candidates in the presidential election planned for 2020 in Poland. The analysis presents the publication as material in a specific issue of the journal, in the situational context (current socio-political events) and as a message with a specific persuasive purpose. The genological characteristics, composition and means of persuasion used by the author were established. In the final part of the analysis, observations related to the readers' reactions to the publication of “Gazeta Wyborcza” were also taken into account.